A Testing of Mahogany Leaf Extract (Swietenia mahagoni) as Antidiabetic Potential In Mice (Mus musculus) Induced by Alloxan - Miracles, Hadasa; Setiawan, Arum; Marisa, Hanifa; Tri Wardana, Singgih; Kamila , Alawiyah (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2025)
Diabetes mellitus is a chronic metabolic disease characterized by hyperglycemia due to impaired secretion or insulin function. Treatment with synthetic drugs often causes side effects so that safer alternatives are needed such as the use of medicinal plants. This study aims to test the potential of mahogany leaf extract (Swietenia mahagoni) as an antidiabetic and determine its optimal dose in mice (Mus musculus) induced by alloxan. The study was conducted in January–March 2025 at the Laboratory of Genetics and Biotechnology and the Laboratory of Animal Biosystematics, Department of Biology, Faculty of Mathematics and Natural Sciences, Sriwijaya University using the Completely Randomized Design (CRD) method. Mahogany leaf extract was obtained through the maceration method using 96% ethanol solvent. Mice were divided into 5 treatment groups, including negative control (aquadest), positive control (glibenclamide 5 mg), and three groups of mahogany leaf extract doses (70, 140, and 280 mg/kgBW). The results showed that mahogany leaf extract had an effect on reducing blood glucose levels in mice. A dose of 70 mg/kgBW gave the highest effect on reducing blood glucose levels (68%), greater than doses of 140 mg/kgBW (60%) and 280 mg/kgBW (65%). The results of the ANOVA test and further Post-hoc test showed significant differences between treatment groups, where the mahogany leaf extract treatment and positive control treatment were significantly different from the negative control. It can be stated that mahogany leaf extract has the potential as an antidiabetic, and the recommended optimal dose is 70 mg/kgBW.